Implementation of Islamic Religious Education Values in Shaping the Character of Students at SD Islam Raudhatul Jannah, Silae Village, Palu City - Mapa, Maulitia J; Naima, Naima; Taufik, Oyan D; Basire, Jumri Hi Tahang (Universitas Pahlawan Tuanku Tambusai, 2025)
Islamic Religious Education is an educational institution that plays a vital role in helping shape the character of students in accordance with Islamic values. Raudhatul Jannah Islamic Elementary School in Silae Village, Palu City, is an Islamic-based elementary school in West Palu. The research observes how the implementation of Islamic Religious Education values and how educators shape the character of students so that they understand and practice the values of Islamic religious education in everyday life. This research uses a descriptive qualitative approach with a case study research design. The data and data sources are primary and secondary data. Data collection techniques include observation, interviews, and documentation. Data analysis is inductive through data reduction, presentation, and verification. Research shows that character building in students involves adopting habits such as praying on time, arriving at school on time, and adhering to rules, which are fundamental to character development. This implementation process takes place not only in the classroom but also through daily activities. The implementation of Islamic religious education values in character formation at Raudhatul Jannah Islamic Elementary School, Palu, involves two main steps: implementation and evaluation.